Method for displaying and observing aggregated niobium compound causing layering and cracking of wheel steel
Patent Information
- Application Number
- CN202411358654.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-14
AI Technical Summary
The existing detection methods cannot clearly display the morphology, size and distribution of the aggregated niobides that cause layered cracking of wheel steel, and cannot effectively solve this problem.
Using a method that includes sampling, grinding, low-magnification display of defects, peeling, mounting, grinding, polishing, etching, scanning electron microscopy observation and energy dispersive spectrometry to determine the composition of the phase, through these steps, the aggregated distribution of niobium compounds can be clearly displayed morphology, size and distribution.
This method can quickly, simply and accurately detect aggregated niobium compounds that cause delamination and cracking of wheel steel. It is low-cost and efficient, and provides a basis for process improvement and quality improvement.
Smart Images

Figure CN119310120A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metallographic analysis and detection, and in particular relates to a method for displaying and observing aggregated niobium compounds that cause delamination and cracking of wheel steel. Background Art
[0002] During the tensile test of wheel steel, fracture delamination was found. The current detection methods mainly focus on scanning electron microscopy analysis and cross-sectional metallography of the fracture. The scanning electron microscopy method can only observe the morphology of the fracture, but cannot observe the morphology, size and distribution of the aggregated niobium compounds that cause delamination and cracking. The cross-sectional metallography method also cannot observe the morphology, size and distribution of the aggregated niobium compounds that cause delamination and cracking. Therefore, it is necessary to create a new detection method that can clearly display the morphology, size and distribution of the niobium compounds that cause delamination and cracking. Summary of the invention
[0003] The technical problem to be solved by the present invention is to provide a method for displaying and observing aggregated niobides that cause delamination and cracking of wheel steel. The method can clearly display the morphology, size and distribution of aggregated niobides that cause delamination and cracking of wheel steel, and can accurately determine the composition of niobides and the atomic ratio of each element through an energy spectrometer. The method has the characteristics of low detection cost, rapidity, simplicity and accuracy.
[0004] In order to solve the above technical problems, the technical solution adopted by the present invention is: A method for displaying and observing aggregated niobium compounds that cause delamination and cracking of wheel steel comprises sampling, grinding, low-magnification defect display, peeling, inlaying, grinding, polishing, corrosion, scanning electron microscope observation and determination of phase composition by energy dispersive spectrometer.
[0005] Furthermore, the specific operations of sampling and grinding described in the present invention are: cutting full-thickness delamination cracking specimens by wire cutting, the specimen size is 15mm×15mm-30mm×30mm; grinding the four cross sections of the cut specimens by a grinder, and then fine grinding them with 280-400-600 sandpaper in sequence, rotating the specimen 90 degrees for each grinding, and then spraying 1.0-2.5 micron polishing agent on a 250mm polishing cloth, polishing at a speed of 900-1400 rpm, sprinkling water while polishing, and polishing for 1-2 minutes.
[0006] Furthermore, the specific operation of low-magnification defect display described in the present invention is: put the ground and polished sample into the etchant 1 for etching, wherein the etchant 1 is prepared by 2 parts of 38% sulfuric acid aqueous solution by volume, 1 part of 20% hydrochloric acid aqueous solution by volume, and 1 part of 5% nitric acid aqueous solution, and the etching time is 2-10 minutes; then put it into the etchant 2 for further etching, wherein the etchant 2 is prepared by 5 grams of sodium metabisulfite, 10 grams of sodium thiosulfate, and 85 milliliters of water, and the etching time is 80-240 seconds, until the surface segregation defect line is revealed, then take it out, rinse it with clean water and blow it dry.
[0007] Furthermore, the specific operation of peeling described in the present invention is: peeling the sample after low-magnification defect display at a position 0.5-1 mm away from the segregation defect line by wire cutting.
[0008] Furthermore, the specific operation of the inlay described in the present invention is: take the sample containing the segregation defect line from the sample peeled by wire cutting, place the sample with the wire cutting surface downward, and use a hot inlay machine for inlay.
[0009] Furthermore, the specific operation of grinding described in the present invention is: putting the mounted sample into an automatic metallographic grinding and polishing machine, using 600# sandpaper and a speed of 900-1400 rpm, grinding for 1-3 minutes until grinding to the surface of the segregation band.
[0010] Furthermore, the specific operation of polishing described in the present invention is: put the ground sample into an automatic metallographic grinding and polishing machine, spray 1.0-2.5 micron polishing agent on a 250mm polishing cloth, polish at a speed of 900-1400 rpm, sprinkle water while polishing, polish for 1-2 minutes, until the surface is bright and scratch-free.
[0011] Furthermore, the etching agent used in the etching of the present invention is prepared by 1 part of 0.01-0.05% HF and 1 part of 0.1-0.5% nitric acid alcohol. The etching time is 1-2 seconds, and then it is rinsed with alcohol and blown dry.
[0012] Furthermore, in the scanning electron microscope observation described in the present invention, the prepared sample is placed under a scanning electron microscope for observation, and the voltage of the electron microscope is 15-20KV.
[0013] The method provided by the present invention abandons the analysis methods of cross-section metallographic and scanning electron microscope fracture, adopts the method of grinding around the sampling, then etching with a low-magnification etching solution to show the segregation defects, peeling from the defects by wire cutting, hot embedding, and then grinding, polishing, etching, and the morphology, size and distribution of the aggregated niobium compounds can be clearly shown under the scanning electron microscope, and the phase composition and atomic ratio are determined by an energy spectrometer.
[0014] The beneficial effects of adopting the above technical solution are: The present invention provides a simple, rapid and low-cost method for displaying and observing the morphology of aggregated niobides that cause delamination and cracking of wheel steel, which can clearly and completely display and observe the morphology, proportion, size and distribution of aggregated niobides, providing a basis for process improvement and quality improvement.
[0015] The method of the invention breaks the traditional cross-section metallographic detection method, adopts low-magnification display of defects first, accurately locates the detection position, and simply and quickly obtains the morphology, size and distribution of the aggregated niobium compounds that cause the delamination and cracking of the wheel steel.
[0016] The method provided by the present invention adopts an etchant prepared by 1 part of 0.01-0.05% HF and 1 part of 0.1-0.5% nitric acid alcohol. The etchant has low cost, is safe and non-toxic, and is convenient to configure. It can clearly and completely display the morphology, size and distribution of aggregated niobium compounds that cause delamination and cracking of wheel steel.
[0017] The method provided by the invention has the characteristics of low detection cost, rapidity, simplicity and accuracy. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 is a morphology of the aggregated niobium compounds in Example 1; Figure 2 This is the spectrometer spectrum of the niobium compounds collected in Example 1; Figure 3 The metallographic image of Comparative Example 1 made by cross-section metallographic method; Figure 4 The fracture morphology obtained by the method of observing the fracture using a scanning electron microscope in comparative example 2; Figure 5 is a morphology image of the aggregated niobium compounds in Example 2; Figure 6 This is the spectrometer spectrum of the niobium compounds collected in Example 2; Figure 7 is a morphology of the aggregated niobium compounds in Example 3; Figure 8 This is the energy spectrometer spectrum of the niobium compounds collected in Example 3. DETAILED DESCRIPTION
[0019] The technical solution of the present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. Example 1
[0020] A method for displaying and observing aggregated niobium compounds that cause delamination and cracking of wheel steel includes sampling, grinding, low-magnification defect display, peeling, inlaying, grinding, polishing, corrosion, scanning electron microscope observation, and energy spectrometer determination of phase composition; specifically: (1) Sampling: Take 1.0mm thick wheel steel (grade 590CL) and cut full-thickness delamination cracking specimens by wire cutting. The specimen size is 15mm×15mm. After the four sections of the cut specimen are flattened by a grinder, they are finely ground with 280-400-600 sandpaper in sequence. The specimen is rotated 90 degrees for each grinding. Then, 1.0 micron polishing agent is sprayed on a 250mm polishing cloth. Polishing is performed at a speed of 900 rpm, and water is sprinkled while polishing for 2 minutes.
[0021] (2) Low-magnification defect display: The sample after grinding and polishing in step (1) is placed in etchant 1 for etching, wherein the etchant 1 is prepared by 2 parts of 35% sulfuric acid aqueous solution by volume, 1 part of 15% hydrochloric acid aqueous solution by volume, and 1 part of 5% nitric acid aqueous solution. The etching time is 10 minutes. Then, the sample is placed in etchant 2 for further etching, wherein the etchant 2 is prepared by 5 grams of sodium metabisulfite, 10 grams of sodium thiosulfate, and 85 milliliters of water. After etching for 80 seconds, the surface segregation defect line is revealed. The sample is taken out, rinsed with clean water, and blown dry.
[0022] (3) Peeling: Use wire cutting to peel off the sample after the defect is shown in step (2) at a position 0.5 mm away from the segregation line.
[0023] (4) Mounting: Take the sample containing segregation lines from the sample peeled by wire cutting, place it with the wire cutting surface facing downward, and use a hot mounting machine for mounting.
[0024] (5) Grinding: Grind the mounted sample using an automatic metallographic grinder, 600# sandpaper, at a speed of 900 rpm, and grind it onto the surface of the segregation zone after 1 minute.
[0025] (6) Polishing: Place the ground sample into an automatic metallographic grinding and polishing machine, spray 1.0 micron polishing agent on a 250 mm polishing cloth, polish at a speed of 900 rpm, sprinkle water while polishing, polish for 2 minutes, and the surface should be bright and scratch-free.
[0026] (7) Corrosion: The corrosive agent is prepared by mixing 1 part of 0.05% HF solution by volume and 1 part of 0.5% nitric acid alcohol solution by volume. Corrode for 2 seconds, then rinse with alcohol and blow dry.
[0027] (8) Scanning electron microscope observation and energy dispersive spectrometer to determine the phase composition: The prepared sample is placed under a scanning electron microscope for observation, using a voltage of 15KV and a magnification of 563 times. The morphology, size and distribution state of the aggregated niobium compounds can be clearly displayed, such as Figure 1 As shown; the composition of niobium compounds can be accurately determined by energy spectrometer, the spectrum is shown in Figure 2 The proportions of each element are shown in Table 1.
[0028]
[0029] Comparative Example 1: Cross-section Metallography The steps for observing the aggregated niobium that causes delamination cracking of wheel steel using cross-sectional metallography are as follows: (1) Mounting sample preparation: Take 1.0mm thick wheel steel (grade 590CL), cut the full thickness delamination cracking specimen by wire cutting, the specimen size is 15mm×15mm, put the specimen vertically into the mounting machine for mounting, the mounted specimen is coarse-fine ground by sandpaper, and then polished. Specifically, water and 2.5μm high-efficiency metallographic polishing agent are evenly sprayed on a 250mm pressure-sensitive rubber wool polishing cloth in turn, and then polished for 2 minutes at a polishing machine speed of 900 rpm.
[0030] (2) Cleaning: Rinse with alcohol for 3 seconds and blow dry.
[0031] (3) Observation under a metallographic microscope: The sample cleaned in step (2) was placed under a ZEISS metallographic microscope for observation. No aggregated niobium compounds that cause delamination and cracking of the wheel steel could be observed. Figure 3 . Comparative Example 1: Method of observing fracture surface using scanning electron microscope
[0032] The method of observing the fracture surface with a scanning electron microscope was used to observe the aggregated niobium compounds that caused the delamination and cracking of the wheel steel. The steps are as follows: (1) Protect the stratified cracked surface with plastic wrap to prevent contamination.
[0033] (2) Use a grinding wheel saw to cut off the fracture.
[0034] (3) Rinse the fracture surface with alcohol.
[0035] (4) Observe under a scanning electron microscope to obtain the fracture morphology, such as Figure 4 shown by Figure 4 It is found that the niobium compound cannot be found to be distributed in a clustered manner and cause delamination cracking. Example 2
[0036] A method for displaying and observing aggregated niobium compounds that cause delamination and cracking of wheel steel includes sampling, grinding, low-magnification defect display, defect peeling, inlaying, grinding, polishing, corrosion, scanning electron microscope observation, and energy dispersive spectrometer determination of phase composition; specifically: (1) Sampling: Take 5.0 mm thick wheel steel (grade 590CL), cut the full thickness delamination cracking sample by wire cutting, the sample size is 15 mm × 15 mm, grind the four cross sections of the cut sample by a grinder, and then use 280-400-600 sandpaper to fine grind in sequence. After each grinding, turn the sample 90 degrees, and then spray 2.5 micron polishing agent on a 250 mm polishing cloth. Polish at a speed of 900 rpm, sprinkle water while polishing, and polish for 1 minute.
[0037] (2) Low-magnification defect display: The sample after grinding and polishing in step (1) is placed in etchant 1 for etching, wherein the etchant 1 is prepared by 2 parts of 38% sulfuric acid aqueous solution by volume, 1 part of 20% hydrochloric acid aqueous solution by volume, and 1 part of 7% nitric acid aqueous solution, and the etching time is 5 minutes; then the sample is placed in etchant 2 for further etching, wherein the etchant 2 is prepared by 6 grams of sodium metabisulfite, 14 grams of sodium thiosulfate, and 80 milliliters of water. After etching for 150 seconds, the surface segregation defect line is revealed, and the sample is taken out, rinsed with clean water, and blown dry.
[0038] (3) Peeling: Use wire cutting to peel the sample after the defect is shown in step (2) at a position 0.8 mm away from the segregation line.
[0039] (4) Mounting: The specimen peeled off by warp cutting is placed with the side containing the segregation line downward and mounted using a hot mounting machine.
[0040] (5) Grinding: The mounted sample is ground using an automatic metallographic grinder, 600# sandpaper, and a speed of 1400 rpm. After 2 minutes, it is ground onto the surface of the segregation zone.
[0041] (6) Polishing: Place the ground sample into an automatic metallographic grinding and polishing machine, spray 2.5 micron polishing agent on a 250 mm polishing cloth, and polish at a speed of 1400 rpm, sprinkling water while polishing. Polish for 1 minute until the surface is bright and scratch-free.
[0042] (7) Corrosion: The corrosive agent is prepared by mixing 1 part of 0.03% HF solution and 1 part of 0.3% nitric acid alcohol solution. Corrode for 1 second, then rinse with alcohol and blow dry.
[0043] (8) Scanning electron microscope observation and energy dispersive spectrometer to determine the phase composition. The prepared sample was placed under a scanning electron microscope for observation. The voltage was 15KV and the magnification was 2040 times. The morphology, size and distribution state of the aggregated niobium compounds can be clearly displayed. Figure 4 As shown; the composition of niobium compounds can be accurately determined by energy spectrometer, the spectrum is shown in Figure 5 The proportions of each element are shown in Table 2.
[0044] Example 3
[0045] A method for displaying and observing aggregated niobium compounds that cause delamination and cracking of wheel steel includes sampling, grinding, low-magnification defect display, defect peeling, inlaying, grinding, polishing, corrosion, scanning electron microscope observation, and energy dispersive spectrometer determination of phase composition; specifically: (1) Sampling: Take 4.0mm thick wheel steel (grade 540CL) and cut the full thickness delamination cracking sample by wire cutting. The sample size is 15mm×15mm. After the four sections of the cut sample are flattened by a grinder, they are finely ground with 280-400-600 sandpaper in sequence. The sample is rotated 90 degrees for each grinding. Then, a 2.5 micron polishing agent is sprayed on a 250mm polishing cloth. Polishing is carried out at a speed of 1400 rpm, and water is sprinkled while polishing for 2 minutes.
[0046] (2) Low-magnification defect display: The sample after grinding and polishing in step (1) is placed in etchant 1 for etching, wherein the etchant 1 is prepared by 2 parts of 40% sulfuric acid aqueous solution by volume, 1 part of 25% hydrochloric acid aqueous solution by volume, and 1 part of 10% nitric acid aqueous solution, and the etching time is 5 minutes; then the sample is placed in etchant 2 for further etching, wherein the etchant 2 is prepared by 8 grams of sodium metabisulfite, 15 grams of sodium thiosulfate, and 77 milliliters of water. After etching for 240 seconds, the surface segregation defect line is revealed, and the sample is taken out, rinsed with clean water, and blown dry.
[0047] (3) Peeling: Use wire cutting to peel the sample after the defect is revealed in step (2) at a position 1.0 mm away from the segregation line.
[0048] (4) Mounting: Take the sample containing segregation lines from the sample peeled by wire cutting, place it with the wire cutting surface facing downward, and use a hot mounting machine for mounting.
[0049] (5) Grinding: The mounted sample is ground using an automatic metallographic grinder, 600# sandpaper, and a speed of 1400 rpm. After 3 minutes, it is ground onto the surface of the segregation zone.
[0050] (6) Polishing: Place the ground sample into an automatic metallographic grinding and polishing machine, spray 2.5 micron polishing agent on a 250 mm polishing cloth, polish at a speed of 900 rpm, sprinkle water while polishing, polish for 2 minutes, and the surface should be bright and scratch-free.
[0051] (7) Corrosion: The corrosive agent is prepared by mixing 1 part of 0.01% HF solution and 1 part of 0.1% nitric acid alcohol solution. Corrode for 1 second, then rinse with alcohol and blow dry.
[0052] (8) Scanning electron microscope observation and energy dispersive spectrometer to determine the phase composition. The prepared sample was placed under a scanning electron microscope for observation. The voltage was 15KV and the magnification was 899 times. The morphology, size and distribution state of the aggregated niobium compounds can be clearly displayed. Figure 6 As shown; the composition of niobium compounds can be accurately determined by energy spectrometer, the spectrum is shown in Figure 7 The proportions of each element are shown in Table 3.
[0053]
Claims
1. A method for displaying and observing aggregated niobium compounds that cause delamination and cracking of wheel steel, characterized in that: It includes sampling, grinding, low-magnification defect display, peeling, mounting, grinding, polishing, corrosion, scanning electron microscope observation and energy spectrometer to determine the phase composition.
2. The method for displaying and observing aggregated niobium compounds that cause delamination and cracking of wheel steel according to claim 1, characterized in that: The specific operation of sampling and grinding is as follows: full thickness delamination cracking specimens are cut by wire cutting, and the specimen size is 15mm×15mm-30mm×30mm; four cross sections of the cut specimens are smoothed by a grinder, and then finely ground with 280-400-600 sandpaper in sequence, with the specimen being rotated 90 degrees for each grinding, and then 1.0-2.5 micron polishing agent is sprayed on a 250mm polishing cloth, and polishing is performed at a speed of 900-1400 rpm, water is sprinkled while polishing, and polishing is performed for 1-2 minutes.
3. The method for displaying and observing aggregated niobium compounds that cause delamination and cracking of wheel steel according to claim 1, characterized in that: The specific operation of the low-magnification defect display shown is: put the ground and polished sample into the etchant 1 for etching, the etchant 1 is prepared by 2 parts of sulfuric acid aqueous solution with a volume concentration of 35-40%, 1 part of hydrochloric acid aqueous solution with a volume concentration of 15-25%, and 1 part of nitric acid aqueous solution with a volume concentration of 5-10%, and the etching time is 2-10 minutes; then put it into the etchant 2 for further etching, the etchant 2 is prepared by 5-8 grams of sodium metabisulfite, 10-15 grams of sodium thiosulfate, and 77-85 milliliters of water, and the etching time is 80-240 seconds, until the surface segregation defect line is revealed, then take it out, rinse it with clean water and blow it dry.
4. The method for displaying and observing aggregated niobium compounds that cause delamination and cracking of wheel steel according to claim 1, characterized in that: The specific operation of peeling is: using wire cutting to peel off the sample after low-magnification defect display at a position 0.5-1 mm away from the segregation defect line.
5. The method for displaying and observing aggregated niobium compounds that cause delamination and cracking of wheel steel according to claim 1, characterized in that: The specific operation of the inlay is: select the sample containing the segregation defect line from the sample peeled by wire cutting, place the sample with the wire cutting surface downward, and use a hot inlay machine for inlay.
6. The method for displaying and observing aggregated niobium compounds that cause delamination and cracking of wheel steel according to claim 1, characterized in that: The specific operation of grinding shown is: put the mounted sample into an automatic metallographic grinding and polishing machine, use 600# sandpaper, and grind at a speed of 900-1400 rpm for 1-3 minutes until it is ground to the surface of the segregation band.
7. The method for displaying and observing aggregated niobium compounds that cause delamination and cracking of wheel steel according to claim 1, characterized in that: The specific operation of the polishing is: put the ground sample into an automatic metallographic grinding and polishing machine, spray 1.0-2.5 micron polishing agent on a 250mm polishing cloth, polish at a speed of 900-1400 rpm, sprinkle water while polishing, polish for 1-2 minutes, until the surface is bright and scratch-free.
8. The method for displaying and observing aggregated niobium compounds that cause delamination and cracking of wheel steel according to claim 1, characterized in that: The etching agent used for the etching is prepared by 1 part of HF solution with a volume concentration of 0.01-0.05% and 1 part of nitric acid alcohol solution with a volume concentration of 0.1-0.5%. The etching time is 1-2 seconds, and then it is rinsed with alcohol and blown dry.
Citation Information
Patent Citations
Method for displaying metallurgical structure of ultralow-carbon cold roll annealed interstitial-free steel
CN101984334A
Method for observing Al5FeSi phase in aluminum-silicon coating original plate alloy layer
CN113533405A
Preparation method of bolt high-power sample
CN114112607A
Economical duplex stainless steel nitride precipitated phase display method
CN115046837A
Method for indicating metallographic texture of gap-free atom cold rolled annealed steel
CN1167257A
Cited By
Precise analysis method for rare earth phase in bottom slag of zinc-aluminum-magnesium production line based on phase structure
CN120404816A
Display method for accurately distinguishing multi-phase structures of W780X hot rolled plate
CN120539141A
Method for precisely distinguishing multiphase structure of w780x hot-rolled plate
CN120539141B